2007
DOI: 10.1002/jor.20419
|View full text |Cite
|
Sign up to set email alerts
|

Torsional strength estimates of femoral diaphyses with endosteal lytic lesions: Dual‐energy x‐ray absorptiometry study

Abstract: Pathologic fracture is a significant problem for individuals with metastatic bone disease. Current guidelines for prophylactic internal fixation are neither reliable nor easily applied. The purpose of this study was to validate dual-energy X-ray absorptiometry (DXA) as an accurate method for estimating torsional bone strength of diaphyseal bone with endosteal lytic lesions. Endosteal lesions of varying sizes were simulated in the diaphyses of 12 adult cadaveric femurs. Unaltered contralateral femurs served as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 58 publications
(82 reference statements)
1
2
0
Order By: Relevance
“…We also tested our hypothesis in different defect sizes (25% versus 50% of bone diameter) and locations (proximal versus distal) across a long bone, indicating that CTRA is location independent, since linear regressions from all sites correlate better with failure torque than aBMD. We did not observe any significant difference among different size holes, a finding also confirmed by Robertson et al (2007), who also showed that lesion size did not correlate with bone strength.…”
Section: Discussionsupporting
confidence: 88%
“…We also tested our hypothesis in different defect sizes (25% versus 50% of bone diameter) and locations (proximal versus distal) across a long bone, indicating that CTRA is location independent, since linear regressions from all sites correlate better with failure torque than aBMD. We did not observe any significant difference among different size holes, a finding also confirmed by Robertson et al (2007), who also showed that lesion size did not correlate with bone strength.…”
Section: Discussionsupporting
confidence: 88%
“…Callus stiffness is the most typical biomechanical indicator of fracture healing. Currently, the in vivo evaluation of callus stiffness involves performing tests for bending [ 11 , 12 ], torsion [ 13 , 14 ], and axial compression [ 15 17 ]. The axial stiffness is a direct measure of the limb’s weight-bearing capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Radiologically, metastatic defects also appear as transcortical holes in long bones. These defects decrease the capacity of 4,17 .…”
Section: Discussionmentioning
confidence: 99%